Structural Insights from HIV-Antibody Coevolution and Related Immunization Studies - Zhou, Jeffrey O. (AIDS Res Hum Retroviruses, 2018)
Human immunodeficiency virus type 1 (HIV-1) is a rapidly evolving pathogen that causes acquired immunodeficiency syndrome (AIDS) in humans. There are ∼30–35 million people infected with HIV around the world, and ∼25 million have died since the first reported cases in 1981. In addition, each year 2–3 million people become newly infected, and >1 million die of AIDS. An HIV-1 vaccine would help halt an AIDS pandemic, and efforts to develop a vaccine have focused on targeting the HIV-1 envelope, Env, found on the surface of the virus. A number of chronically infected individuals have been shown to produce antibodies, called broadly neutralizing antibodies (bnAbs), that target many strains of HIV-1 by binding to Env, thus suggesting promise for HIV-1 vaccine development. BnAbs take years to develop, and have a number of traits that inhibit their production; thus, a number of researchers are trying to understand the pathways that result in bnAb production, so that they can be elicited more rapidly by vaccination. This review discusses results and implications from two HIV-1-infected individuals studied longitudinally who produced bnAbs against two different sites on HIV-1 Env, and immunization studies that used Envs derived from those individuals.